Phytoseiid mites of the subtribes Typhlodromalina and Euseiina (Acari: Phytoseiidae: Euseiini) from subSaharan Africa - Moraes, G.D.; Zannou, I.D.; Oliveira, A.R.; Yaninek, John S.; Hanna, R. (2006)
Twenty-four phytoseiid species of the subtribe Typhlodromalina Chant & McMurtry are reported in this paper. They refer to all species of this subtribe now known to occur in sub-Saharan Africa, and they belong to the general Amblydromalus Chant & McMurtry (5 species), Prasadromalus Chant & McMurtry (1 species), Typhlodromalus Muma (7 species) and Ueckermannseius Chant & McMurtry (11 species). Ten of these species are described for the first time and 11 species are redescribed. All of these were collected in cassava habitat, in an effort to determine the mites of that agro-ecosystem in that region. Redescriptions are based mostly on specimens collected in this study; for 6 species, redescriptions are also based on type specimens. A key to help in the separation of Typhlodromalina presently known to occur in sub-Saharan Africa is included. The morphological relation between a group of sub-Saharan species of Euseius (2 of which first described in this paper) and Ueckermannseius is also discussed.